(untitled) (Context: Journal of Interdisciplinary Studies, 2024)
Freedom of religion and the right to equality and non-discrimination are significant human and fundamental rights that are currently under-researched in the Finnish context. This article analyses how different legislative and societal structures adversely affect the realisation of positive religious freedom for Muslims in Finland by examining two case studies: freedom of religion among Muslim prisoners, and the impermissibility of headscarves as part of the police uniform. The article argues that although Finnish legislation does not directly limit freedom of religion, it contains structures that hinder the realisation of positive religious freedom for Muslims. These stem from the close relationship between the state and the Evangelical Lutheran Church, and from prejudicial attitudes that manifest together or separately. Such structures may lead to an unequal position for Muslims compared to Christians in society, and can constitute discrimination.